A Study on Prevalence of Life-Style Diseases and Its Risk Factors in Urban Area of Jamnagar City - Sochaliya, Kishor M; Parmar, Dipesh V; Yadav, Sudha B (National Journal of Community Medicine, 2012)
Introduction: Chronic diseases of life-style particularly Hypertension, DM and CHD account for millions of deaths each year globally. These diseases share similar modifiable risk factors, including tobacco smoking, alcohol consumption, hyperlipidaemia, physical inactivity, obesity etc. so that identifying and modifying these risk factors have been recommended as a strategy for their prevention and control in various settings. Aim- To find out the prevalence of common life style diseases and their risk factors Method: A cross sectional study was done, which was containing 450 male respondents in the age group of 35-45 years from Patel colony in Jamnagar city. Predesigned and prestructured questionnaires covering socio-economic aspects, dietary pattern, smoking, alcohol intake, physical activity, personality and parental history of hypertension and diabetes were reviewed. In addition some anthropometric measurements (e.g., height, weight and BMI) and clinical measurements (e.g., blood pressure) were also done. Result: The overall prevalence rate for the common life-style diseases was observed to be 33.56% for hypertension, 10.44% for diabetes mellitus and 44.44% for overweight/obesity. The few major risk factors noted among participants were high fatty diet (99.11%), high salt intake (96.67%) and Type A personality (71.33%). About 2/5th (38 %) of them were current smokers and only 2% were consuming alcohol. 42.22% of the target population were physically inactive based on work and leisure time activities. While around 69.33% of the respondents were having a positive family history of hypertension and/or diabetes. Conclusion: The study demonstrated a high prevalence of life-style diseases and their risk factors. Serious consideration should be given to this escalating burden of lifestyle diseases in the study population. The development and implementation of relevant health promotion and intervention programmes that will improve the general health and reduce the risk for NCDs in this population are advised.